The Theoretical Aspects of Anti-Crisis Management of Economic System - Rubakha Mariya V. (Bìznes Inform, 2017)
The article is concerned with an analysis of the mechanism for anti-crisis management of economic system. A comparative analysis and a theoretical separation between the concepts of «anti-crisis management» and of «crisis management» were accomplished. A mechanism for the anti-crisis management of economic system has been proposed and the author’s definition of this mechanism has been provided. A considerable attention has been given to the criteria for the presence of crisis events. The normative, comparative, socio-cultural approaches, and a dynamic model of existing socio-economic tendencies in diagnosing crisis together with the depth of crisis tendencies in economic systems, have been allocated. The possibilities and prospects for implementing mechanisms, technologies and methods of anti-crisis management were analyzed; a number of priority measures for anti-crisis management and directions for reforming the mechanism for anti-crisis management of economic system have been proposed; the factors that reduce the efficiency of the anti-crisis management in Ukraine in the current environment have been determined.